Impact of Migration on Economic and Social Development : A Review of Evidence and Emerging Issues - Ratha, Dilip; Mohapatra, Sanket; Scheja, Elina (2012)
This paper provides a review of the literature on the development impact of migration and remittances on origin countries and on destination countries in the South. International migration is an ever-growing phenomenon that has important development implications for both sending and receiving countries. For a sending country, migration and the resulting remittances lead to increased incomes and poverty reduction, and improved health and educational outcomes, and promote economic development. Yet these gains might come at substantial social costs to the migrants and their families. Since many developing countries are also large recipients of international migrants, they face challenges of integration of immigrants, job competition between migrant and native workers, and fiscal costs associated with provision of social services to the migrants. This paper also summarizes incipient discussions on the impacts of migration on climate change, democratic values, demographics, national identity, and security. In conclusion, the paper highlights a few policy recommendations calling for better integration of migration in development policies in the South and the North, improving data collection on migration and remittance flows, leveraging remittances for improving access to finance of recipient households and countries, improving recruitment mechanisms, and facilitating international labor mobility through safe and legal channels.